Quantum dot light emitting devices for photomedical applications. Issue 3 (10th April 2017) - Chen, Hao; He, Juan; Lanzafame, Raymond; Stadler, Istvan; Hamidi, Hamid El; Liu, Hui; Celli, Jonathan; Hamblin, Michael R.; Huang, Yingying; Oakley, Emily; Shafirstein, Gal; Chung, Ho‐Kyoon; et al.
Abstract: While OLEDs have struggled to find a niche lighting application that can fully take advantage of their unique form factors as thin, flexible, lightweight and uniformly large‐area luminaire, photomedical researchers have been in search of low‐cost, effective illumination devices with such form factors that could facilitate widespread clinical applications of photodynamic therapy (PDT) or photobiomodulation (PBM). Although existing OLEDs with either fluorescent or phosphorescent emitters cannot achieve the required high power density at the right wavelength windows for photomedicine, the recently developed ultrabright and efficient deep red quantum dot light emitting devices (QLEDs) can nicely fit into this niche. Here, we report for the first time the in‐vitro study to demonstrate that this QLED‐based photomedical approach could increase cell metabolism over control systems for PBM and kill cancerous cells efficiently for PDT. The perspective of developing wavelength‐specific, flexible QLEDs for two critical photomedical fields (wound repair and cancer treatment) will be presented with their potential impacts summarized. The work promises to generate flexible QLED‐based light sources that could enable the widespread use and clinical acceptance of photomedical strategies including PDT and PBM. Abstract : Ultra‐bright quantum dot light‐emitting devices (QLEDs) have been proposed as light sources for photomedicine. An initial in vitro study demonstrated that QLEDs can increase cell metabolism over control systems or kill cancerous cells efficiently. Development of low‐cost, flexible, disposable QLEDs with specific wavelengths to match the absorption peaks of photomedical sensitizers is expected to enable wide clinical acceptance of photomedicine.